Lead-cadmium oxyfluoride glasses and glass-ceramics - Silva, MAP; Briois, V; Poulain, M.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Natl Inst Optoelectronics, 2002)
Glasses and glass-ceramics have been obtained in oxyfluoride systems involving lead and cadmium fluorides and one of the well-known glass former oxides SiO2, B2O3 and TeO2. Vitreous domains were established and a wide range of compositions including high heavy metal contents lead to stable glasses. Amorphous structures have been studied by short-range order spectroscopy techniques (Raman scattering and x-ray absorption) and molecular basic structures have been identified. Besides the usual oxides, the role of glass former could also be proposed for cadmium ions. Special attention has been paid for crystallization process. Cubic lead fluoride, cubic lead tellurite, tetragonal tellurium oxide and a solid solution of the type Pb1-xCdxF2 are obtained as crystallization products depending on the composition and temperature of heat treatments. Pb1-xCdxF2 solid solutions are well known superionic materials and obtaining this solid solution as a crystal phase could be very interesting for applications concerning ionic electrical conduction properties. The addition of rare earth ions led to the control of the crystallization process. In the presence of the nucleating ion only the cubic form beta-PbF2 was identified. Rare earth ions are present in the crystal phase and crystal-like spectroscopic properties were observed suggesting interesting applications for these perfectly transparent glass ceramics in photonics.
Keywords: oxyfluoride glasses; glass-ceramics; structure